Infusing Circular Reporting Model and Creative Marketing Mix for a Progressive Orange Economy: A Study with reference to Creative Business Units in Karnataka, India in the Post Covid-19 Pandemic - Venkatesh, Sneha; M, Anand Shankar Raja; M, Athmaramani; L, Mynavathi; M, Amaravathi (Asian Journal of Interdisciplinary Research, 2023)
The orange economy which is also known as the creative economy has been an unrecognized industry though it has been a major contributor to economic growth and development. In this research an introspection has been done on four major economic factors such as: Choice of creativity with available resources, Marketing the good with unique strategies, Supply chain of good and services and tackling the demand fluctuations. These four factors rule the creative economy and hence the interlink between all these factors and its impact on the success of orange economy has been discussed in this research. The data has been collected from 30 small-owned creative business units which are spread across Karnataka. An interview schedule has been conducted with the creative business owners to understand the creative business units and its functionality. The structured interview has three layers which include (layer 1: questions related to creative business, layer 2: impact of Covid-19 pandemic on creative business units and layer 3: questions related to marketing, promotion and sales strategies used by creative business units. All the collected data has been exposed to a manual qualitative content coding to find new variables, new themes, cause, and effect and to construct a new conceptual model. The model has been suggested to the creative business units for active consideration and implementation. If the creative business units make use of the suggested marketing mix and strategies, they will be able to sustain themselves in the post-Covid-19 pandemic.